Banjar Regency Ulama's Perspective on Buying and Selling Nira Water in Trees and Review According to Muamalah Jurisprudence - Rizki Nurramadhina; Muhammad Fazrianur Arridho; Anwar Hafidzi; Muhammad Noor Ridani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Nira water is a natural resource that is rich in benefits and has high economic potential because it can be made into various kinds of food. In the process of buying and selling nira water in trees carried out by the community, the buyer must pay a certain amount of money to utilize the nira water in the tree without knowing how much nira water he will get. This raises questions about the law of this activity through a review of Islamic law. This research examines the practice of buying and selling nira water in trees with a focus on the aspects of Islamic law. in the tree with a focus on its Islamic legal aspects. Through an empirical legal research method with a legal sociology approach based on direct observations and approach based on the results of direct observation and The results of this study show that the law of the practice of buying and selling nira water in trees is not legal. practice of buying and selling nira water in trees is not valid because in this practice there is an element of gharar, namely the uncertainty of the transaction resulting from the uncertainty of the transaction. uncertainty resulting from the non-fulfillment of sharia provisions in the transaction. The impact of transactions that contain gharar. The impact of transactions that contain gharar is the element of oppression of one of the parties. The impact of transactions that contain gharar is the element of oppression of one of the parties to the transaction.